The effect of partially fluorinated chain length on the mesomorphic properties of chiral 2', 3'-difluoroterphenylates. Issue 14 (7th December 2020) - Herman, Jakub; Aptacy, Albert; Dmochowska, Ewelina; Perkowski, Paweł; Kula, Przemysław
ABSTRACT: The homologous series of the new antiferroelectric liquid crystals, containing 2ʹ, 3ʹ-difluorosubstituted terphenyl as the mesogenic core have been synthesised and evaluated. The synthetic routes with their mesomorphic properties were described. Also other physical properties are delivered. The liquid crystal phases were preliminarily determined by thermomicroscopic and microcalorimetric measurements and verified by dielectric measurements and miscibility methods. The temperatures and enthalpies of the phase transitions are given. Graphic abstract: uf0001